Food policy, nutrition and nutraceuticals in the prevention and management of COVID-19: Advice for healthcare professionals - Ayseli, Yasemin Ipek; Aytekin, Nazli; Buyukkayhan, Derya; Aslan, Ismail; Ayseli, Mehmet Turan (ELSEVIER SCIENCE LONDON, 2020)
Background: The 2019 novel coronavirus (2019-nCoV) represents an ongoing major global health crisis with a potentially unprecedented death toll and socio-economic impact in the modern era. Measures taken to reduce the rate of transmission are too unprecedented, but are deemed necessary. The extensive strain on public health services has meant that individual agency is increasingly called for. To support this, there is a need to review policy and procedure governing the food and commerce industries in particular. Additionally, it is necessary to convey a more comprehensive and nuanced understanding of relevant diet and lifestyle factors to both healthcare practitioners and the general public. Scope and approach: To our knowledge, a review of possible additional measures for healthcare proffesionals, which includes the possible nutritional management COVID-19 pandemic does not yet exist. Key Findings and Conclusions: This review identifies i) changing trends in consumer awareness and purchasing patterns in response to COVID-19, and their potential future implications for the food and food-commerce industry ii) problematic elements of policy relevant to the outbreak of COVID-19, including the handling of wildlife and food-commerce, ii) newly emergent technologies in food science which represent viable and costeffective means to reduce the risk of transmission of coronavirus, such as anti-microbial packaging, iii) important nutritional considerations with regard to coronavirus disease prevention and management, including nutrition in early infancy, and the role of select micronutrients (vitamins and minerals), phytochemicals and probiotics in conferring protection against both viral infection and pathogenicity.
Keywords: COVID-19; Immunity; Antiviral; Micronutrients; Nutraceuticals; Nutrition; GLUTATHIONE-PEROXIDASE; TRANS-RESVERATROL; IMMUNE-RESPONSES; VITAMIN-C; MELATONIN; BIOAVAILABILITY; QUERCETIN; SUPPLEMENTATION; DEFICIENCY; METABOLISM; Food Science & Technology